Porous chitosan-based nanocomposites containing gold nanoparticles. Increasing the catalytic performance through film porosity - Bonardd, Sebastian; Ramirez, Oscar; Abarca, Gabriel; Leiva, Ángel; Saldías, César; Díaz, David Díaz (International journal of biological macromolecules, 2022)
The preparation of porous and non-porous chitosan thin-films containing gold nanoparticles was carried out, aiming to evaluate the effect of porosity on their catalytic response using the p-nitrophenol reduction as model reaction. To achieve this, both types of samples were decorated with gold nanoparticles having similar characteristics in terms of amount, size and shape, which were synthesized following a two-step adsorption-reduction process. The results demonstrated that the presence of porosity generates a considerable enhancement of the catalytic property. This behavior is reflected in higher kinetic constant and conversion values, along with a better recyclability after consecutive cycles. The inclusion of porosity in nanocomposites afforded kobs values 7.5 times higher than the non-porous material, as well as conversion values as high as 80 % in <20 min. On the other hand, as an additional experiment, a porous sample prepared with half the amount of gold also exhibited a better performance than the non-porous catalyst, revealing that the porosity allowed to decrease the amount of catalytic metal used and still exhibiting kobs values 5.9 times higher than the non-porous specimen. These studies demonstrate that there is an important synergistic support-nanostructure relationship, which strongly influences the performance of the nanomaterial.